Knee adduction moment decomposition: Toward better clinical decision-making - Baniasad, Mina; Martin, Robin; Crevoisier, Xavier; Pichonnaz, Claude; Becce, Fabio; Aminian, Kamiar (Frontiers in Bioengineering and Biotechnology, 2022)
Knee adduction moment (KAM) is correlated with progression of medial knee osteoarthritis (OA). ‎Although a generic gait modification can reduce the KAM in some patients, it may have a reverse ‎effect on other patients. We proposed the “decomposed ground reaction vector” (dGRV) model to 1) ‎distinguish between the components of the KAM and their contribution to the 1st and 2nd peaks, and ‎KAM impulse and 2) examine how medial knee OA, gait speed, and a brace influence these ‎components. Using inverse dynamics as reference, we calculated the KAM of 12 healthy participants ‎and 12 patients with varus deformity and medial knee OA walking with/without a brace and at three ‎speeds. The dGRV model divided the KAM into four components defined by the ground reaction force ‎‎(GRF) and associated lever-arms described with biomechanical factors related to gait modifications. ‎The dGRV model predicted the KAM profile with a coefficient of multiple correlations of 0.98±0.01. The ‎main cause of increased KAM in the medial knee OA group, the second component (generated by the ‎vertical GRF and mediolateral distance between knee and ankle joint centers), was decreased by the ‎brace in the healthy group. The 1st peak increased, and KAM impulse decreased with increasing ‎velocity in both groups, while no significant change was observed in the 2nd peak. The four-component ‎dGRV model successfully estimated the KAM in all tested conditions. It explains why similar gait ‎modifications produce different KAM reductions in subjects. Thus, more personalized gait ‎rehabilitation, targeting elevated components, can be considered.‎